Management Classroom Learning In The School EBF Cristal - Antonio Guterres; Inacia Tamele; Julio Pereira; João Sancho Pires; Tonico de Jesus (Green Publisher Indonesia, 2025)
This research realized in EBF Cristal with his principal objective to know about the model of classroom management that used by school leader and teacher in the school. Throught this research, the researchers can find and write that the school leader and teachers demonstrated classroom management based on the existence of National curriculum in Timor-Leste: central methode for student, utilized two (2) languages Portuques and Tetun with the simple words to fasilitated student to understand about content that they teach for. Classroom management encompasses a variety of skills and techniques that teachers can use to create a high-performing learning environment. At its core, it aims to ensure classes run smoothly, disruptive behavior from students is kept to minimum and teaching materials and activities promote learning. The ultimate goal is to ensure that both the students and the teacher get the most out of the classroom experience. Good classroom management should aim to: Create an organised and functional environment for the teacher and students, Establish opportunities for academic learning and personal growth, Reduce bad classroom behaviour and other disruptions, Be time-efficient and ensure learning time is always prioritized, Make sure students are focused, motivated, and productive and Promote an inclusive environment that caters for all ability levels.